2008
DOI: 10.1590/s0100-204x2008000600001
|View full text |Cite
|
Sign up to set email alerts
|

Banco de sementes em cerrado sensu stricto sob queimada e sistemas de cultivo

Abstract: O objetivo deste trabalho foi avaliar o efeito de queimada e de sistemas de cultivo sobre o banco de sementes em solo de Cerrado. Foi realizada amostragem em área sob cerrado sensu stricto queimada e não queimada, assim como em área de pastagem e lavoura com preparo convencional do solo. Não houve redução no banco de sementes, embora tenha havido menor número de espécies e de famílias, e dos índices de diversidade, com a queimada. Houve maior índice de valor de importância (IVI) e número de espécies nativas, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 15 publications
1
25
1
9
Order By: Relevance
“…The formation of a seed bank represents an important regeneration strategy for many weed species from this family (LECK; SCHÜTZ, 2005). This result corroborates similar studies conducted in other tropical regions, such as those from Kamoshita et al (2010), who observed that 86% of the species present in the seed banks of 22 rice fields from smallholders in Cambodia were from the Cyperaceae family.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The formation of a seed bank represents an important regeneration strategy for many weed species from this family (LECK; SCHÜTZ, 2005). This result corroborates similar studies conducted in other tropical regions, such as those from Kamoshita et al (2010), who observed that 86% of the species present in the seed banks of 22 rice fields from smallholders in Cambodia were from the Cyperaceae family.…”
Section: Discussionsupporting
confidence: 92%
“…The density of 372 viable seeds m -2 found in the weed seed bank assessed in the greenhouse is lower compared to the 22,313 seeds m -2 in lowland areas and 6,768 seeds m -2 in a crop rotation (soybean, fallow, bean) reported by Carmona (1995) Isaac and Guimarães (2008). This is probably due to management practices that the smallholder farmers from Lago Verde County have been using in the past ten years.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Various studies recently conducted in the tropics have been aimed at identifying weed species in crop fields, in pastures and in the corresponding seed banks (Silva & Dias-Filho 2001;Lacerda et al 2005;Begum et al 2006;Lopes et al 2006;Ikeda et al 2008;Isaac & Guimarães 2008;Andrade et al 2009;Costa et al 2009;Kamoshita et al 2010). However those studies were focused on agribusiness rather than on generating scientific knowledge for use in subsistence farming.…”
Section: Introductionmentioning
confidence: 99%